Long working hours in the healthcare system of the Belo Horizonte municipality, Brazil: a population-based cross-sectional survey - Juliana M. Andrade; Ada A. Assunção; Mery N. S. Abreu (BMC, 2017)
Abstract Background Health personnel are key players in developing and improving healthcare systems, caring for individuals and their communities, and helping improve quality of life. However, these professionals are often exposed to long working hours because of the pressing need for their services at potentially any time of day. The long working hours they endure are a major risk factor for both acute and chronic health problems. The present study aimed to analyze occurrences of long working hours and their association with individual characteristics and employment factors among workers in the municipal healthcare system in Belo Horizonte, Brazil. Methods In this cross-sectional study, a ramdomly selected proportional sample of 1549 participants was analyzed from among the total of 13 602 workers in the Belo Horizonte municipal healthcare system in 2009. "Long" working hours were defined as >44 h/week. A self-administered questionnaire was used for accumulating data. Associations with outcomes were estimated using logistic regression, in univariate and multivariate models. Results The rate of occurrence of long working hours was 31.4% (95% CI 29.1-33.7). Lower educational level (high school, technical, or uncompleted undergraduate [OR 0.60, 95% CI 0.47-0.78 p < 0.001], or elementary [OR 0.33, 95% CI 0.19-0.55 p < 0.001]) was associated with a lower likelihood of self-reporting long working hours in relation to the group with the highest educational level (completed undergraduate or postgraduate). Male sex (OR 1.62, 95% CI 1.26-2.09 p < 0.001), having children (PR 1.54, 95% CI 1.20-1.97 p = 0.001), and being in the healthcare provider group (OR 1.82, 95% CI 1.40-2.35 p < 0.001) were factors associated with greater likelihood of long working hours. Conclusions It was observed that number of long weekly working hours was related to individual characteristics and employment factors.